Prevalence of hearing screening failures in low‐risk childhood cancer survivors. Issue 2 (2nd December 2021) - Phelan, Meghan; Hayashi, Susan S.; Sauerburger, Kara; Henry, Jennifer; Wu, Ningying; Hayashi, Robert J.
Abstract: Background: We sought to estimate the frequency of hearing screening failures in pediatric cancer survivors at low risk for hearing loss and evaluate the feasibility of administering screenings in this population. Procedure: Survivors in the St. Louis Children's Hospital Late Effects Clinic were recruited. Eligibility included (a) diagnosis of a pediatric cancer treated without platinum chemotherapy or cranial radiation, (b) at least 6 months from completion of therapy, (c) between the ages of 7 and 18 years, (d) cognitively/behaviorally able to participate, and (e) English speaking. Behavioral hearing screenings from 1000 to 8000 Hz were performed by trained personnel using a calibrated audiometer. A failed screen was defined by a participant not responding to two or more of the three screening attempts for at least one frequency in at least one ear. Results: One hundred nine patients met eligibility criteria with 78 enrolled (71.5%). Diagnoses included leukemia (57.7%), sarcoma (11.5%), Wilms tumor (14.1%), lymphoma (12.8%), and other solid tumors (3.9%). The median age was 13.2 years (Q1–Q3: 9.6–15.4) and the median time from treatment completion was 3.7 years (Q1–Q3: 2.3–7.4). Eighteen patients (23%) failed the hearing screen (95% CI: 14%–34%). No demographic or treatment‐related variables were significantly correlated to screening failure. Six screen failures (33%) underwent formal audiology assessments, with three demonstrating unilateral hearing loss: two conductive and one sensorineural. Conclusions: A significant fraction of pediatric cancer survivors at low risk for hearing loss failed hearing screening. Broader use of hearing screening should be considered.